Bovine tuberculosis in domestic pigs: Genotyping and distribution of isolates in Argentina - Barandiaran, Soledad; Martinez Vivot, Marcela; Pérez, Andrés M.; Cataldi, Angel Adrian; Zumarraga, Martin Jose (Elsevier, 2020)
Bovine tuberculosis is caused by Mycobacterium bovis and affects primarily cattle, among many other mammal species. In this study, 250 isolates of M. bovis collected from pigs slaughtered in Argentina were typed by spoligotyping. Over half of the isolates (66%) grouped into two spoligotypes.